Fintech Waqaf: Solusi Permodalan Perusahaan Startup Wirausaha Muda - Muhamad Nafik Hadi Ryandono (Jurnal Studi Pemuda, 2018)
Money waqaf in Indonesia has a huge potential. Despite the fact, this huge potential has not been organized and utilized optimally by the waqaf management agency. Another problem faced in waqaf money is the difficulties in integrate the system of funding, financing, mauquf alaih, and distribute the beneficiaries. In the present era, waqaf in Indonesia has not been digitalized and has not used the Financial Technology (FinTech) system, so it is less economically and inefficient. The expected benefits of the research are waqaf can be a solution to the capital problems that have been faced by start-up companies which mostly un-bankable. In other side, it hopefully can encourage Nadzir to be involved in growing and developing entrepreneurship for youth starting with establishing a start-up company. This research approach is qualitative descriptive. The data is primary data with data collection techniques namely focus group discussions and interviews. The objects of the research are 30 youth start-ups in Surabaya. The result of study is that money waqf can be an alternative solution of capital problems for youth start-up companies who are un-bankable. The Sharia Financial Technology (SFT) system is a system that capable of integrating nadzir with Islamic Financial Institutions Accep Cash Waqf (IFIACW), funding, financing, mauquf alaih, start-up investors, Islamic Financing Guarantee Institution (IFGI) and Islamic Banks.